Novel Strategies to Optimize the Amplification of Single-Stranded DNA - Nehdi, Atef; Samman, Nosaibah; Aguilar-Sánchez, Vanessa; Farah, Azer; Yurdusev, Emre; Boudjelal, Mohamed; Perreault, Jonathan (Frontiers in Bioengineering and Biotechnology, 2020)
The generation of single stranded DNA plays a key role in in vitro selection of DNA aptamers and in other molecular techniques such as DNA sequencing and microarrays. Here we describe three novel methodologies for ssDNA production and amplification. Furthermore, we describe some previously unnoticed aspects of random DNA amplification. Our results showed that in asymmetric PCR the addition of a high melting temperature reverse primer blocked at its 3′ end by a dideoxy nucleotide drives the reaction further towards ssDNA production. We demonstrated also that incorporation of internally inverted nucleotide/(s) in one primer can be used as a new method of polymerization termination. Using such modified primer, the PCR product includes two complementary DNA strands having different lengths and separable from one another by denaturing gel electrophoresis. In addition, we showed that nicking enzymes can be used to cleave the undesirable strand allowing the isolation of the target ssDNA strand.